Intravitreal injection of anti-Interleukin (IL)-6 antibody attenuates experimental autoimmune uveitis in mice. (August 2017) - Tode, Jan; Richert, Elisabeth; Koinzer, Stefan; Klettner, Alexa; Pickhinke, Ute; Garbers, Christoph; Rose-John, Stefan; Nölle, Bernhard; Roider, Johann
Highlights: New treatment possibility for Experimental Autoimmune Uveitis (EAU). Intravitreal anti-IL-6 injections attenuate EAU. EAU activity is correlated with ocular IL-6 and IL-17 levels. Abstract: Purpose: To evaluate the effect of an intravitreally applied anti-IL-6 antibody for the treatment of experimental autoimmune uveitis (EAU). Methods: EAU was induced in female B10.RIII mice by Inter-Photoreceptor-Binding-Protein (IRBP) in complete Freund's adjuvant, boosted by Pertussis toxin. Single blinded intravitreal injections of anti-IL-6 antibody were applied 5–7 days as well as 8–10 days (3 day interval) after EAU induction into the randomized treatment eye and phosphate buffered saline (PBS) into the fellow control eye. Clinical and fluorescein angiography scoring (6 EAU grades) was done at each injection day and at enucleation day 14. Enucleated eyes were either scored histologically (6 EAU grades) or examined by ELISA for levels of IL-6, IL-17 and IL-6 soluble Receptor (sIL-6R). Results: Uveitis developed in all 12 mice. Clinical uveitis score was significantly reduced (p = 0.035) in treated eyes (median 2.0, range 0–4.0, n = 12) compared to the fellow control eyes (median 3.0, range 1.0–4.0, n = 12). Angiography scores were reduced in 9/12 treated eyes and histological scores in 3/4 treated eyes compared to the fellow control eyes. Cytokine levels were determined in 8 mice, of which 4 responded to anti-IL-6 treatment and 4 did not respond. All mice responding to treatment had a significant reduction of IL-6 (p < 0.01) and IL-17 (p = 0.01) levels in treated eyes compared to the fellow control eyes. This difference was not seen in non-responding mice. Conclusions: Intravitreal anti-IL-6 treatment significantly attenuates experimental autoimmune uveitis in mice. EAU activity correlates with ocular IL-6 and IL-17 levels.